LanI-Mediated Lantibiotic Immunity in Bacillus subtilis: Functional Analysis - Geiger, Christoph (Appl Environ Microbiol, 2019)
Lantibiotics subtilin and nisin are produced by Bacillus subtilis and Lactococcus lactis, respectively. To prevent toxicity of their own lantibiotic, both bacteria express specific immunity proteins, called SpaI and NisI. In addition, ABC transporters SpaFEG and NisFEG prevent lantibiotic toxicity by transporting the respective peptides to the extracellular space. Although the three-dimensional structures of SpaI and NisI have been solved, very little is known about the molecular function of either lipoprotein. Using laser-induced liquid bead ion desorption (LILBID)–mass spectrometry, we show here that subtilin interacts with SpaI monomers. The expression of either SpaI or NisI in a subtilin-nonproducing B. subtilis strain resulted in the respective strain being more resistant against either subtilin or nisin. Furthermore, pore formation provided by subtilin and nisin was prevented specifically upon the expression of either SpaI or NisI. As shown with a nisin-subtilin hybrid molecule, the C-terminal part of subtilin but not any particular lanthionine ring was needed for SpaI-mediated immunity. With respect to growth, SpaI provided less immunity against subtilin than is provided by the ABC transporter SpaFEG. However, SpaI prevented pore formation much more efficiently than SpaFEG. Taken together, our data show the physiological function of SpaI as a fast immune response to protect the cellular membrane. IMPORTANCE The two lantibiotics nisin and subtilin are produced by Lactococcus lactis and Bacillus subtilis, respectively. Both peptides have strong antimicrobial activity against Gram-positive bacteria, and therefore, appropriate protection mechanisms are required for the producing strains. To prevent toxicity of their own lantibiotic, both bacteria express immunity proteins, called SpaI and NisI, and in addition, ABC transporters SpaFEG and NisFEG. Whereas it has been shown that the ABC transporters protect the producing strains by transporting the toxic peptides to the extracellular space, the exact mode of action and the physiological function of the lipoproteins during immunity are still unknown. Understanding the exact role of lantibiotic immunity proteins is of major importance for improving production rates and for the design of newly engineered peptide antibiotics. Here, we show (i) the specificity of each lipoprotein for its own lantibiotic, (ii) the specific physical interaction of subtilin with its lipoprotein SpaI, (iii) the physiological function of SpaI in protecting the cellular membrane, and (iv) the importance of the C-terminal part of subtilin for its interaction with SpaI.